Menstrually-related stabbing headache in a patient without migraine: case report - Valença, Marcelo Moraes; Silva-Néto, Raimundo Pereira (Headache Medicine, 2022)
Introduction Stabbing headache is considered a primary headache and is a prevalent entity in the general population. Objective To present an unusual case of stabbing headache associated with menstruation. Method Data collected through complete anamnesis. Case report The authors report a case of a woman suffering from a stabbing headache which features that has not been previously described – a menstrual pattern in the presentation of stabbing headache attacks. Conclusions We conclude that this menstrual pattern of stabbing headache attacks is unusual in patients with primary stabbing headache and that it does not fulfil diagnostic criteria for migraine or tension-type headache.